Development of a Flipped Medical School Dermatology Module. Issue 5 (May 2017) - Fox, Joshua; Faber, David; Pikarsky, Solomon; Zhang, Chi; Riley, Richard; Mechaber, Alex; O'Connell, Mark; Kirsner, Robert S.
Abstract : Objectives: The flipped classroom module incorporates independent study in advance of in-class instructional sessions. It is unproven whether this methodology is effective within a medical school second-year organ system module. We report the development, implementation, and effectiveness of the flipped classroom methodology in a second-year medical student dermatology module at the University of Miami Leonard M. Miller School of Medicine. Methods: In a retrospective cohort analysis, we compared attitudinal survey data and mean scores for a 50-item multiple-choice final examination of the second-year medical students who participated in this 1-week flipped course with those of the previous year's traditional, lecture-based course. Results: Each group comprised nearly 200 students. Students' age, sex, Medical College Admission Test scores, and undergraduate grade point averages were comparable between the flipped and traditional classroom students. The flipped module students' mean final examination score of 92.71% ± 5.03% was greater than that of the traditional module students' 90.92% ± 5.51% ( P < 0.001) score. Three of the five most commonly missed questions were identical between the two cohorts. The majority of students preferred the flipped methodology to attending live lectures or watching previously recorded lectures. Conclusions: The flipped classroom can be an effective instructional methodology for a medical school second-year organ system module. Abstract : The flipped classroom model is a form of learning in which students learn basic concepts before class and use their classroom time to discuss the material and apply the concepts with faculty input/instruction. The authors describe the implementation of the flipped classroom design for a medical school second-year module and compare students' mean final examination scores and satisfaction with the flipped classroom course to the previous year's traditional, lecture-based course.